2021
DOI: 10.1107/s2056989021006642
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and Hirshfeld surface analysis of a pyrrolo-thiazine complex

Abstract: In the title compound, diethyl 2,2-dioxo-4-(thiophen-2-yl)-1-[(thiophen-2-yl)methyl]-3,4,6,7,8,8a-hexahydro-1H-pyrrolo[2,1-c][1,4]thiazine-1,3-dicarboxylate, C22H28NO6S3, the pyrrolo ring is in an envelope conformation while the thiazine ring adopts a near chair conformation. The dihedral angles between the thiazine ring and the methylthienyl, thienyl and pyrrolo rings are 64.0 (2), 87.92 (7) and 5.6 (2)°, respectively. In the crystal, the molecules are linked by weak C—H...O hydrogen bonds. A Hirshfeld surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In a study concerning the packing features of simple alkanes, Spackmann and McKinnon found a disordered structure of butane featuring the central sharp spike on the diagonal of the fingerprint plot . This seems to be a rather common appearance and is caused by overemphasized contacts of dynamically or statically disordered C–H groups to neighboring molecules. The second type, the doubling of this central spike as found here in II (compared with Figure ), can be explained similarly, with the addition, that the intersection of disordered molecule parts simulate donor–acceptor interactions with an impact on the resulting d e and d i values. , Neighboring disordered alkyl chains also produce this effect frequently. , The third type is particularly puzzling, as in this study it appears in a disordered Z ′ = 2 structure ( II at 150 K, see the Supporting Information), but rather sparsely, hinting at lowly weighted contributions. This raises the question if this is just the second type again but in combination with multiple independent molecules in the asymmetric unit.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…In a study concerning the packing features of simple alkanes, Spackmann and McKinnon found a disordered structure of butane featuring the central sharp spike on the diagonal of the fingerprint plot . This seems to be a rather common appearance and is caused by overemphasized contacts of dynamically or statically disordered C–H groups to neighboring molecules. The second type, the doubling of this central spike as found here in II (compared with Figure ), can be explained similarly, with the addition, that the intersection of disordered molecule parts simulate donor–acceptor interactions with an impact on the resulting d e and d i values. , Neighboring disordered alkyl chains also produce this effect frequently. , The third type is particularly puzzling, as in this study it appears in a disordered Z ′ = 2 structure ( II at 150 K, see the Supporting Information), but rather sparsely, hinting at lowly weighted contributions. This raises the question if this is just the second type again but in combination with multiple independent molecules in the asymmetric unit.…”
Section: Resultsmentioning
confidence: 51%
“…44−47 The second type, the doubling of this central spike as found here in II (compared with Figure 8), can be explained similarly, with the addition, that the intersection of disordered molecule parts simulate donor− acceptor interactions with an impact on the resulting d e and d i values. 48,49 Neighboring disordered alkyl chains also produce this effect frequently. 50,51 The third type is particularly puzzling, as in this study it appears in a disordered Z′ = 2 structure (II at 150 K, see the Supporting Information), but rather sparsely, hinting at lowly weighted contributions.…”
Section: Intermolecular Interactions 431 Hirschfeld Surface Compariso...mentioning
confidence: 99%